Implementasi Etika Islam pada Sektor-Sektor Ekonomi Masyarakat Muslim - Nafi'ah Nafi'ah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2018)
A number of fundamental pillars (fundamental) in relation to the value system of Islamic business ethics that developed from efforts to reinterpretation of the Qur’an and sunnah. Concepts are directed to further elevate moral values relating to the prevention of exploitative measures, flowering, speculation, gambling, and waste that have been formulated by experts. The concept of business ethics is vital for the implementation of economic activities starting from the process of production, distribution, consumption to achieve of humanity.